Role of organizational ethics in sustainable development: a conceptual framework - Wesarat, Phathara-on; Sharif, Mohmad Yazam; Abdul Majid, Abdul Halim (SustaiN Society, 2017)
The focus of many organizations worldwide has been changing from greater productivity and profit maximization to sustainable development. Those organizations that focus on profit-only often make shortterm decisions without concern for long-run sustainable benefits.The concept of organizational ethics has been widely discussed as it may provide the means to long-term business success. This paper considers the basis of organizational ethics as an integration of ethical climate and culture in organizations that has an important impact on ethical decision-making and outcomes, which in turn could lead to sustainable development. The challenge of businesses is to remain ethical to stakeholders under conditions of uncertainty. They are expected to serve sustainable development not only for the benefits of themselves, but also the interests of others in society.